Pedagogical Competence of Pre-Service Teachers’ of English Department Mulawarman University During Online Teaching Practice - Iqbal Iman; Weningtyas Parama Iswari; Dian Anggriyani (E3L: Journal of English Language Teaching, Linguistics, and Literature, 2023)
The teacher’s level of competence is one of the factors that directly affect the quality of teaching and consequently student’s performance. This study aimed to know the implementation of teacher’s pedagogical competence of English Department students as pre- service teacher of PLP 2021, and to find out which pedagogical competence aspects that the English Department students as pre-service teacher of PLP 2021 implemented in their teaching practice. This study employed qualitative descriptive research by using interview guidelines and note-taking from the lesson plans and teaching videos. The research subjects for this study were the English Department students who followed PLP 2021, by the total of six subjects. In order to collect and analyze the data, the researcher used interactive data analysis which consists of data reduction, data display, and drawing conclusion/verification. The findings of this study revealed that the research subjects (2018 English Department students of Mulawarman University) have different efforts to conduct teaching English according to their own knowledge and skill. In addition, it is known that the students did not implement all aspects of pedagogic competence while writing the lesson plans and making/searching the teaching videos to be used in their teaching practice. Therefore, the researcher suggested the English Department students to understand the level of pedagogic competence that they have